How Social Assistance Affects Subjective Wellbeing: Lessons from Kyrgyzstan. Issue 4 (3rd April 2022) - Gassmann, Franziska; Martorano, Bruno; Waidler, Jennifer
Abstract: This paper investigates the effects of social assistance on subjective well-being looking at the case of Kyrgyzstan. For this purpose, we exploit recent changes in the design of social assistance and apply a difference in difference (DiD) method combined with an inverse probability weighting (IPW) technique. In contrast to the existing literature, we find that in the short-term, the receipt of social assistance benefits is associated with lower levels of subjective well-being. Our findings also reveal that participation in social assistance leads to some reduction in satisfaction regarding recipients' own economic conditions. Moreover, we find that the negative effects on subjective well-being disappear for the oldest generations, which experienced the dissolution of the Soviet Union. By contrast, the effect is negative for the youth, who grew up in a new society where needing help is ultimately the responsibility of the individual citizen. For individuals with high trust in political institutions, the negative effect of state intervention does not hold, while it persists in case of low trust in political institutions.